EU democracy promotion in the Mediterranean: cooperation against all odds? - Hüllen, Vera van (2009)
Abstract: "Focusing on the Euro-Mediterranean relations since the early 1990s, this paper investigates in how far the EU has been able to shape its relations with third countries according to its democracy promotion policy. The paper traces the evolution of the EU's provisions for democracy promotion and compares the implementation of political dialogue and democracy assistance with seven (semi-)authoritarian regimes (Algeria, Egypt, Jordan, Lebanon, Morocco, Syria, and Tunisia) since the early 1990s. A clear regional trend to more intensive cooperation lends credibility to the claim that the EU possesses a certain agenda setting power in international relations. A systematic comparison across countries and over time explores the explanatory power of interdependence, political liberalisation, and statehood for the remaining country variation. The paper finds that the degree of political liberalisation in target countries is the most important scope condition for cooperation in the field of d